Evaluation of residual stresses induced by high speed milling using an indentation method - Díaz, F. V. (2012)
Fil: Díaz, F. Universidad Tecnológica Nacional. Facultad Regional Rafaela. Departamento de Ingeniería Electromecánica-Departamento de Ingeniería Industrial (UTN-FRR); Argentina